Sifat Panggilan Allah: Studi Terhadap Panggilan Allah Kepada Abraham Dalam Kejadian 12:1-4 - Kasiatin Widianto (Jurnal Teologi dan Pelayanan Kerusso, 2017)
God's call to Abraham is written in Genesis 12: 1-9 occurred after two heart-wrenching events of God, namely the Flood (Genesis 6 and 7) and the events of the Tower of Babel (Genesis 11), in which the wickedness of man was great and every inclination of his heart sesalu only evil-eye, therefore God destroy. Post these events God chose Abraham, it is like dew in the desert, which is soothing. His election was a saving grace in the midst of punishment that should be passed to humans. Call of God revealed to Abraham as a person, but the impact covering all the face of the earth, where it appears in it how the nature of God's call to him, the Private nature, Separation nature, and Agreement nature.